Karate Sport Management in Jombang District - Zen, Mohammad Zaim; Saputro, Arnaz Anggoro (Universitas Majalengka, 2024)
Karate in Jombang has decreased achievements and results that need to improve in the 2021 and 2023 PORPROV events, as seen from the medal acquisition data. From these problems, the author researched the management function of karate sports in Jombang Regency. This research uses a qualitative descriptive method—data collection in this study is done through interviews, questionnaires, and documentation. Data analysis is done by reducing, presenting, and drawing conclusions. The results of research on karate sports management in Jombang in 2023 are: 1) Karate sports planning is in a suitable category, 2) Organizing karate sports is in a suitable category, 3) The implementation of karate sports is in the moderate category, 4) Controlling karate sports is in the moderate category. The suggestion of this research is to suggest to the INKAI Jombang management in managing karate sports to improve the quality and continue to strive to maintain the quality of an already good organization by applying aspects of management science so that it can achieve INKAI Jombang's mission of making karate a superior sport in Jombang.